(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The purpose of the National Active Lifestyle Strategy is to raise proportion of physically active people in Hungary. It also sets goals to reduce the time spent sitting, and, following the World Health Organization (WHO) recommendations, to achieve a minimum of 150–300 minutes of moderate-intensity physical activity (PA) per week for adults, and a minimum of 60 minutes of moderate-vigorous PA per day for children. Policy Description: In order to support evidence-based policy making, the Active Lifestyle Survey was conducted at the turn of 2023–24 on a national representative sample of the adult population, which will be one of the main monitoring tools in the future. The Strategy endorses the WHO PA recommendations and sets the goal of reducing the percentage of adults never practising sports by 15% by the year 2035. The baseline value for monitoring has been set by the 2023/2024 Active Lifestyle Survey, which found that 55% of the Hungarian adult population never practice sport. Besides the Active Lifestyle Survey, which will be the main monitoring tool of the Strategy, and which focuses on the characteristics, motivations, and perceived barriers to PA, the data sources used for reporting PA prevalence for the WHO-EU PA country factsheets, notably the European Health Interview Survey for adults and the Health-Behaviour Survey of Children, remain as main data sources in the near future. Dissemination and communication of the Strategy is already ongoing. Monitoring activities will be coordinated and handled in an integrated way, trying to create synergies among the already existing data sources and the newly established Active Lifestyle Survey, which is planned to be repeated every four years. Monitoring of the Strategy needs to be harmonised, using also the existing monitoring tools that are parallelly in place. The Active Lifestyle Survey will be the basic reference to monitor the success of the Strategy, while the activities and data reported in the framework of the EU-WHO HEPA Focal Network will be an integral part of the monitoring measures as well.